PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI SARANA PROMOSI TERHADAP KEMAJUAN DESTINASI WISATA DI KABUPATEN BUTON - Wa Nur Fida; Muh. Rizal Ardiansyah Putra; Muh Hidayatullah; Jundi Syahrul Ramadan (JURNAL PENGABDIAN MANDIRI, 2024)
Using information and communication technology, we can easily find out information or have direct contact with everyone in all corners of the world. Information technology as a means of promoting tourist destinations takes shape and form in increasing the progress of a region, especially in the field of economic income. So far, regional governments or tourist destination managers still lack understanding regarding the use of information technology as a means of promoting tourist destinations as progress in increasing visitors and income in economic growth and income of regions and local communities. So far, they have promoted tourism destinations using direct communication from conversations between people who have visited tourist destinations. Therefore, there is community service to increase the progress of tourism destinations by teaching the government or tourist destination managers as promotional media that can be used by young people and become progress and improvements in these tourist destinations